Net blotch of barley (Hordeum vulgare), caused by Drechslera teres and its effect on yield - Petta, A.; Lavilla, M. (Agronomía Mesoamericana, 2022)
Introduction. Barley (Hordeum vulgare) net blotch (MR) causes yield losses estimated between 23 % to 44 %, as well as its malting quality. Objective. To evaluate over time the evolution of net blotch in different malting barley cultivars with and without application of foliar fungicide, associating it with yield and malting quality. Materials and methods. The trial was carried out during 2017 at the experimental field Universidad Nacional del Noroeste of the Buenos Aires province, in the city of Junín (Bs. As., Argentina) with an experimental block design with a 5x2 factorial arrangement and three repetitions, with randomization within blocks. Factor 1 was the cultivars and factor 2 was the foliar fungicide treatment. The pathometric variables incidence and severity were used to calculate the intensity of the MR and subsequently the area under the disease intensity progress curve (ABCPIE). Results. There was no interaction between cultivars and foliar fungicide application. The application of the foliar fungicide allowed a decrease in the ABCPIE in all the cultivars evaluated. Caliper was significantly associated (R2=0.67; p<0.0001) and inversely proportional to ABCPIE. Conclusions. The temporal evolution of the MR depended on the cultivar. Sinfonia had the lowest ABCPIE compared to the other cultivars evaluated. The application of foliar fungicide significantly reduced the evolution of MR over time. The disease influenced yield components and industrial quality of malting barley.